Viktimisasi Ganda Perempuan Sebagai Korban Kekerasan Dalam Rumah Tangga (Studi Kasus Keluarga X Dan Y Di Bangkinang Kota) - Widya Ramailis, Neri; Lutpi , Muhammad (SISI LAIN REALITA, 2021)
This study aims to analyze and obtain the causes and objective description of the Multiple Victimization of Women as Victims of Domestic Violence. The method used is a qualitative method with a descriptive type with the research location located in Bangkinang City. In order to obtain information, the informants were set as sources of direct data information by means of interviews. All data collected were analyzed descriptively to be further concluded as a result of the research found. The results of research on double victimization of women as victims of domestic violence. It was found that the presence of domestic violence in the Bangkinang City was caused by the behavior of the husband who did not work and was drunk. Then it was resolved to the police as a form of deterrent effect on the partner, namely the husband who committed violence and some were resolved amicably. Then it was found that there were at least 3 causes of violence, namely physical violence, psychological violence, and economic violence. Of the three causes that trigger domestic violence in Bangkinang City.